The Impact of The Presence of the University of Timor on the Economy of Local Communities in North Central Timor District - Pangastuti, Margareta Diana; Naihati, Elfrida Desiderata (International Journal of Economics (IJEC), 2024)
In the last decade, the North Central Timor Regency in East Nusa Tenggara Province has become a new center of economic growth. This is due to the presence of a higher education institution known as the University of Timor. The presence of this university has a positive impact on small and medium businesses due to the significant flow of educational migration. Therefore, this research aims to identify the partial or simultaneous influence of three main variables, namely social and cultural patterns, educational accessibility, and community thought patterns and attitudes, on the welfare of people involved in micro, small, and medium enterprises (MSMEs). ). The analytical method used is multiple linear regression, involving a sample of 100 respondents from a total of 693 MSME actors. Sampling was carried out randomly using the Simple Random Sampling technique based on the Slovin formula. The research results show that these three variables have a significant positive effect on the welfare of MSMEs in the North Central Timor Regency.